Promotion Strategy of Rajawali Indonesia Event Organizer in Increasing the Number of Audiences for Prambanan Jazz Festival 2023 Post COVID-19 - Gumay, Devi Qorotaayun; Mulawarman, Krisna (Universitas Muhammadiyah Surakarta, 2023)
This research aims to describe qualitatively Rajawali Indonesia's strategy of using a promotion mix such as Advertising, Public Relations, Sales promotion, Personal Selling, and Direct Marketing after COVID-19 including using endorsement services through influencers, displaying advertisements on various media platforms including printed media newspapers and magazines, outdoor media billboards, social media Instagram, Tik-Tok, Twitter, Facebook and other media such as radio and television, media partners and local communities to attract the interest of the wider community. To test the validity of the data, researchers used the triangulation method. The results showed that Rajawali Indonesia successfully utilized all tools in the digitalization era for promotional activities and used the promotion mix as a marketing communication model to increase the number of spectators to >45.000 per day at the Prambanan Jazz Festival 2023.